IDENTIFICATION BY RP-HPLC-DAD OF NATURAL DYESTUFFS FROM LAKE PIGMENTS PREPARED WITH A MIXTURE OF WELD AND DYER'S OAK DYE PLANTS - (:unkn) unknown (TAYLOR & FRANCIS INC, 2012)
The lake pigments by means of the weld (Reseda luteola) and dyer's oak (Quercus infectoria) dye plants were prepared by using KAl(SO4)(2)center dot 12H(2)O (alum), FeSO4 center dot 7H(2)O and SnCl2 center dot 2H(2)O mordants. A reversed-phase high performance liquid chromatography (RP-HPLC) with diode array detection (DAD) method was utilized for the identification of dyestuffs present in the lake pigments. The dyestuff extractions from the pigments were carried out with a solution mixture of 37% HCl:MeOH:H2O (2:1:1, v/v/v). The performed method is able to analyze and detect natural dyestuffs such as luteolin, apigenin, gallic acid, and ellagic acid present in the lake pigments.
Keywords: dyer's oak; lake pigment; luteolin; natural dyestuff; Reseda Luteda; RP-HPLC; RESEDA-LUTEOLA L.; LIQUID-CHROMATOGRAPHY; TEXTILES; ICONS